Sphenoid sinuses’ volume and area analysis of Brazilian individuals’ CBCTs, related to sex, age, skin color, and nutritional status using DDS-Pro™ software - Barros, Franciéllen de [UNESP] (2024)
The purpose of this study was to analyze the volume and area of sphenoid sinuses of Brazilian individuals’ cone-beam computed tomography (CBCT) images using the beta version of the DDS-Pro™ 2.14.2_2022 software (DPP Systems, Czestochowa, Poland), to assess a potential correlation to sex, age, skin color, and nutritional status, and to evaluate differences between the right and left sides. Three-dimensional volume and area measurements were made with the software using CBCT images of 113 living Brazilian individuals of both sexes (67 females and 46 males). TEM, rTEM, and R were used to assess the reproducibility of inter- and intra-examiner measurements. The measurement means were estimated with 95% confidence intervals according to sex and age group. There were no significant differences between the left and right sides for both volume and area and between the sexes and black and white individuals. Volume and area were significantly higher in 18 years or older (p < 0.05) and in individuals with normal body mass index (BMI) (p < 0.05). The obtained results do not allow indicating the use of sphenoid sinuses volume and area measurements to estimate sexual dimorphism, and the same occurred for skin color. However, such measures can help to estimate age. Further studies are suggested with a larger sample, especially for the nutritional status variable.